Hubungan Glukosa Darah Terhadap Proses Penyembuhan Luka Pasca Operasi di Rumah Sakit Sumber Waras Jakarta - Amalia Riana; Jeffrey Jeffrey (Jurnal Kesehatan, 2021)
Surgery is an invasive treatment of the part of the body to be treated, opened, or exposed which is usually done through an incision. After certain actions are carried out, the operation will end with closure and suturing of the wound. The bactericidal activity of leukocytes is reduced in patients with diabetes mellitus with poor glucose control so that it can cause complications related to wound healing. This study aims to assess the relationship of blood glucose to the postoperative wound healing process at Sumber Waras Hospital, Jakarta. This study uses observational analytical research methods. The data used in the form of data collected from medical records, namely; age, gender, blood sugar, postoperative wound healing process, and years. The data were analyzed using univariate analysis to provide a descriptive picture of the distribution of frequencies, averages, and media from the data obtained. Bivariate analysis to determine the relationship between blood glucose and postoperative wound healing. Bivariate analysis was performed using the Chi-Square test. Based on medical record data of patients who have undergone surgery, there were 66 respondents. The age of the respondents ranged from 25-60 years with an average age of 55 years. Most of the respondents were female as many as 39 people (59%). The distribution of blood sugar levels of most respondents was abnormal blood glucose levels as many as 38 people with a percentage of 57%. Based on bivariate results with Chi-square analysis, it is known that the p-value is 0.048 <0.05. It can be concluded that there is a significant relationship between blood glucose to the postoperative wound healing process.